Role of oral physician in diagnosis of occult disease of primary hyperparathyroidism - Shraddha C Jugade; Supriya Bhalchim; Amey Karkhanis (Wolters Kluwer Medknow Publications, 2022)
Parathyroid hormone (PTH) plays a key role in the regulation of calcium homeostasis. It is secreted by a pair of parathyroid glands located behind the thyroid gland. Primary hyperparathyroidism is the disorder which is seen in 0.2%-0.3% of the population. It is the third most common endocrine disorder after Diabetes Mellitus and Thyroid disorders. There are several systemic manifestations of the disease including skeletal, Renal, abdominal, neurological ones. The following case report discusses some of the classic oral manifestations of the disease and signifies the role of an Oral physician in the diagnosis of underlying systemic disorder.